Doped and modified sodium ion layered metal oxide positive electrode material as well as preparation method and application thereof

By doping modified sodium ion layered metal oxide positive electrode material, the sodium ion content and the proportion of doped elements are reduced, the calcination airflow parameters and adhesive composition are optimized, the existing material structure is unstable and the residual alkali is high, the circulation, magnification and safety performance of the battery are improved, and the industrial production and promotion of sodium ion batteries are promoted.

CN119542409AActive Publication Date: 2025-02-28TIANJIN ZHONGDIAN NEW ENERGY RES INST CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411698415.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-13
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing sodium ion layered metal oxide positive electrode materials have unstable structure during charging and discharging, with high residual alkali, and the preparation process has high requirements for environmental temperature and humidity, which is not conducive to industrial production and promotion and application.

Method used

The doped modified sodium ion layered metal oxide positive electrode material, specifically NazNi0.3Fe0.3Mn0.3AxByO2, is used to improve the structural stability and battery performance of the material by adjusting the sodium ion content and the proportion of doped elements A and B, and to optimize the calcination airflow parameters and improve the adhesive composition.

Benefits of technology

It improves the structural stability of the material and the cycle, magnification and safety performance of the battery, reduces the environmental requirements of the residual alkali and preparation process, making sodium ion batteries more suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542409A_ABST
    Figure CN119542409A_ABST
Patent Text Reader

Abstract

The invention relates to a doped modified sodium ion layered metal oxide positive electrode material and a preparation method and application thereof, the positive electrode material is Na0. 9Ni0. 3Fe0. 3Mn0. 3AxByO2 obtained by cation doping, x + y is 0.1, x is more than or equal to 0 and less than or equal to 0.1, y is more than or equal to 0 and less than or equal to 0.1, and z is more than or equal to 0.8 and less than or equal to 0.9; the doping aims to improve the structural stability, reduce residual alkali and improve the multiplying power and circulation, and the prepared metal oxide is a blocky (flaky) single-crystal-like layered material and has a smooth and round surface; meanwhile, the cycle performance and the safety performance of the battery can be improved. And an adhesive formed by mixing polyvinylidene fluoride and polyacrylonitrile is selected when the pole piece is prepared, so that the stability of the positive electrode of the battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ions, and in particular relates to a doped and modified sodium ion layered metal oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the new energy industry, especially the rapid development of the new energy vehicle industry, the price of lithium resources has risen rapidly. In addition, the uneven distribution of lithium resources around the world has caused the price of lithium resources to remain high. Therefore, resource and cost issues have become bottlenecks restricting the healthy development of new energy. Therefore, it is urgent to develop alternative products for lithium resources. Sodium-ion batteries have become another technical hotspot for the development of new energy due to their abundant sodium resources. Sodium ranks sixth in the element content in the earth's crust, and it is widely distributed and has low development costs. Therefore, sodium-ion batteries are an effective alternative to lithium-ion batteries.

[0003] The key to sodium-ion batteries lies in sodium-ion cathode materials. Sodium-ion cathode materials include polyanion cathode materials, layered metal oxide cathodes (Na x MO2, M = one or more metal elements among Fe, Mn, Co, Cr, Ni, Ti, V, Al, Mg, Zr, Zn, Cu, W, Ca, Sn, B, Mo, Nb, Tc, etc.), Prussian blue and other materials. Among them, layered metal oxide positive electrode materials are most likely to be promoted and used on a large scale and can be industrialized quickly. Layered metal oxide positive electrodes are divided into P2 type and O3 type. Among them, P2 type positive electrode materials have better kinetic properties due to their large interlayer spacing; O3 type positive electrode materials have higher capacity due to their high sodium content. At present, the structure of layered metal oxide positive electrode materials is unstable during the charging and discharging process, the residual alkali is high, and the preparation process has high requirements for environmental temperature and humidity, which is not conducive to industrial production and promotion and application. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a doped and modified sodium ion layered metal oxide positive electrode material and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is: a doped and modified sodium ion layered metal oxide positive electrode material, the active material is material Na z Ni 0.3 Fe 0.3 Mn 0.3 A x B y O2, x+y=0.1, 0≤x≤0.1, 0≤y≤0.1, 0.8≤z≤0.9; wherein A and B are one of Al, Cu, Mg, Zn, Co, Ca, B, Ti, Zr, Sn, Mo, W, Tc, Nb, Ag, V, Ba and Sr.

[0006] Preferably, after the raw materials of the active material are mixed, they are placed in an air atmosphere or an oxygen atmosphere and calcined at 900° C., and the flow rate of the air atmosphere or the oxygen atmosphere is adjusted to adjust the active material of the positive electrode material.

[0007] Preferably, the flow rate adjustment parameter is that the flow rate of the upper atmosphere valve is set to 3-5m 3 / h, the flow rate of the lower atmosphere valve is set to 4-7m 3 / h.

[0008] A sodium ion battery positive electrode includes a positive electrode material.

[0009] Preferably, the slurry for preparing the positive electrode also includes superconducting carbon black, carbon nanotube and graphene composite conductive agent, adhesive and solvent; wherein the mass ratio of active material, conductive agent and adhesive is 92-96:1-3:3-5.

[0010] Preferably, the adhesive is a mixture of polyvinylidene fluoride and polyacrylonitrile in a mixing ratio of 1:0.25-4.

[0011] Preferably, the mixing ratio of polyvinylidene fluoride and polyacrylonitrile in the adhesive is 4:6.

[0012] Preferably, the solvent is N-methylpyrrolidone.

[0013] A sodium ion battery includes a sodium ion battery positive electrode.

[0014] The advantages and positive effects of the present invention are: by improving the sodium ion content in the sodium ion layered metal oxide material to reduce the alkalinity of the material surface, doping new elements, and improving the structural stability of the material, the prepared positive electrode material can improve the cycle, rate and safety performance when used in a sodium battery;

[0015] In addition, the performance of the positive electrode sheet can be further optimized by improving the composition and proportion of the binder in the positive electrode material electrode sheet, thereby further improving the stability of the sodium battery; thereby improving the cycle of the sodium ion battery and enabling large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a SEM image of the O3 sodium ion layered metal oxide positive electrode material prepared in Comparative Example 1 of the present invention;

[0017] Figure 2 This is a SEM image of the O3 sodium ion layered metal oxide positive electrode material prepared in Example 1 of the present invention;

[0018] Figure 3 This is a SEM image of the O3 sodium ion layered metal oxide positive electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0019] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0020] The present invention relates to a doped and modified sodium ion layered metal oxide positive electrode material and a preparation method and application thereof. The cation doped and modified O3 type sodium ion battery positive electrode material is Na z Ni 0.3 Fe 0.3 Mn 0.3 A x B y O2, x+y=0.1, 0≤x≤0.1, 0≤y≤0.1, 0.8≤z≤0.9. The sodium content is reduced from the common 1 to 0.8-0.9. After doping modification, the capacity will not decrease too much, the residual alkali is significantly reduced, and the structural stability is improved. Among them, A and B are one or more elements of Al, Cu, Mg, Zn, Co, Ca, B, Ti, Zr, Sn, Mo, W, Tc, Nb, Ag, V, Ba, Sr. The main function of A and B elements is to improve the structural stability and air stability of the material and improve the cycle and rate characteristics.

[0021] In certain embodiments of the present invention, air or O2 is introduced during the sintering process, and the moisture, residual alkali, specific surface area and morphology of the finished material are precisely controlled by adjusting the gas flow rate. When the sintering atmosphere is O2, a mixed gas doped with O2 can be used, and the oxygen content is not less than 50%.

[0022] The O3 type sodium ion battery positive electrode material prepared by the above method can be made into a sodium battery positive electrode, and can be further assembled into a sodium battery. In certain embodiments of the present invention, the battery performance can be further improved by adjusting the components of the adhesive when preparing the positive electrode sheet. PVDF (polyvinylidene fluoride) and PAN (polyacrylonitrile) in different proportions are mixed as a binder for the positive electrode sheet to improve the bonding force between the positive electrode sheet and the current collector. The ratio of PVDF to PAN ranges from 20% to 80%, thereby improving the problems of poor processing performance and poor bonding caused by the high alkalinity of the surface of the sodium ion layered metal oxide positive electrode material. Preferably, when PVDF:PAN=40%:60%, the bonding force of the positive electrode sheet can ensure the cycle performance of the battery cell while ensuring the processing performance, which is beneficial to improve the safety of the battery.

[0023] Compared with the prior art, this solution reduces the sodium content from 1 to 0.9, which can ensure that the residual alkali is reduced without affecting the battery capacity. And as the sodium content decreases, ion vacancies will appear in the material, which can easily lead to impurity phases in the material structure, affecting the structural stability, rate and cycle performance of the material; in this solution, the structural stability, rate and cycle performance of the material are improved by doping bimetallic materials. However, the sodium ion layered oxide material itself is unstable in the air and is prone to gelation during the electrode manufacturing process. Therefore, by improving the binder in the positive electrode slurry, the selection of polyvinylidene fluoride and polypropylene can improve the slurry's tolerance to air.

[0024] After doping with specific metal elements, different roasting gas flow parameters will affect the purity of the material and the change of residual alkali on the surface. In this scheme, the air flow adjustment parameters are limited, that is, the tunnel furnace is used for roasting. The air flow parameters of the upper valve in the tunnel furnace are set to a flow rate of 3-5m 3 / h, the flow rate of the lower atmosphere valve is set to 4-7m 3 / h for calcination control. The materials prepared by the improved method have been tested, and the surface residual alkali, structural stability, rate and cycle performance have been improved.

[0025] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.

[0026] Comparative Example 1: Positive Electrode Material Na 0.9 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2

[0027] Weigh the Na 0.9 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 Manganese tetraoxide, ferric oxide, nickelous oxide, and sodium carbonate were mixed evenly and sintered at 900°C for 18 hours in an air atmosphere. The prepared positive electrode material was tested by scanning electron microscopy. The results are as follows Figure 1 As shown, it can be seen that the material is a block-like (sheet-like) single crystal layered material structure with a smooth surface.

[0028] When it is prepared as a positive electrode active material, the positive electrode active material is Na 0.9 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3O2, the conductive agent is a composite of superconducting carbon black (super P), carbon nanotubes (CNT) and graphene (Graphene), of which superconducting carbon black is 75%, carbon nanotubes are 20%, and graphene is 5%; the composite conductive agent is 80% carbon nanotubes and 20% graphene; the binder is polyvinylidene fluoride (PVDF), and the solvent is N-methylpyrrolidone (NMP). Among them, the preset mass ratio of active material, conductive agent and binder is: (94±2): (2±1.0): (4±1.0).

[0029] Example 1: Doped modified O3 type sodium ion positive electrode material Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.1 O2

[0030] Weigh the Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.1 Manganese tetraoxide, ferric oxide, nickelous oxide, sodium carbonate, and zinc oxide in an O2 stoichiometric ratio are mixed evenly and sintered at 900°C for 18 hours in an oxygen atmosphere (with an oxygen content of not less than 50%). The residual alkali, BET, oxygen defects, and morphology of the material are regulated by adjusting the gas flow rate. The prepared positive electrode material is examined by electron microscopy, and the structure is as follows Figure 2 As shown, it can be seen that the material is a block (sheet) single crystal layered material structure with a smooth surface, indicating that the doping elements have entered the crystal lattice.

[0031] When it is prepared as a positive electrode active material, the positive electrode active material is Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.1 O2, the conductive agent is a composite of superconducting carbon black (super P), carbon nanotubes (CNT) and graphene (Graphene), of which superconducting carbon black is 75%, carbon nanotubes are 20%, and graphene is 5%; the binder is polyvinylidene fluoride (PVDF), and the solvent is N-methylpyrrolidone (NMP). Among them, the preset mass ratio of active material, conductive agent and binder is (94±2): (2±1.0): (4±1.0).

[0032] Example 2: Doped modified O3 type sodium ion positive electrode material Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Mg 0.05 O2

[0033] Weigh the Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Mg 0.05 Manganese tetraoxide, ferric oxide, nickelous oxide, sodium carbonate, zinc oxide, and magnesium oxide in an O2 stoichiometric ratio are mixed evenly and sintered at 900°C for 18 hours in an oxygen atmosphere (with an oxygen content of not less than 50%). The residual alkali, BET, oxygen defects, and morphology of the material are controlled by adjusting the gas flow rate. The prepared positive electrode material is detected by electron microscopy, and the structure is as follows Figure 3 As shown, it can be seen that the material is a blocky (sheet-like) single crystal layered material structure, and the surface is still smooth, indicating that the co-doped elements have entered the crystal lattice.

[0034] When it is prepared as a positive electrode active material, the positive electrode active material is Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Mg 0.0 5O2, the conductive agent is a composite of superconducting carbon black (super P), carbon nanotubes (CNT) and graphene (Graphene), of which superconducting carbon black is 75%, carbon nanotubes are 20%, and graphene is 5%; the binder is polyvinylidene fluoride (PVDF), and the solvent is N-methylpyrrolidone (NMP). Among them, the preset mass ratio of active material, conductive agent and binder is (94±2): (2±1.0): (4±1.0).

[0035] Example 3: Doped modified O3 type sodium ion positive electrode material Na 0.85 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.1 O2

[0036] Weigh the Na 0.85 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.1 Manganese tetraoxide, ferric oxide, nickelous oxide, sodium carbonate and zinc oxide in an O2 stoichiometric ratio are mixed evenly and sintered at 900°C for 18 hours in an oxygen atmosphere (oxygen content not less than 50%); the residual alkali, BET, oxygen defects and morphology of the material are controlled by adjusting the gas flow rate.

[0037] The positive electrode active material was prepared according to the method of Example 1.

[0038] Example 4: Doped modified O3 type sodium ion positive electrode material Na 0.8 Ni0.3 Fe 0.3 Mn 0.3 Zn 0.1 O2

[0039] Weigh the Na 0.8 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.1 Manganese tetraoxide, ferric oxide, nickelous oxide, sodium carbonate and zinc oxide in an O2 stoichiometric ratio are mixed evenly and sintered at 900°C for 18 hours in an oxygen atmosphere (oxygen content not less than 50%); the residual alkali, BET, oxygen defects and morphology of the material are controlled by adjusting the gas flow rate.

[0040] The positive electrode active material was prepared according to the method of Example 1.

[0041] Example 5: Preparation of sodium battery

[0042] The positive electrode active materials prepared in Comparative Example 1 and Examples 1-5 were prepared into sodium batteries according to the following method. The specific method is as follows:

[0043] The first step is homogenization: the positive electrode active material, conductive agent, binder and dispersant are mixed according to a preset mass ratio and stirred evenly, and then dissolved in a solvent for dispersion. By adjusting the amount of added solvent, the solid content of the positive electrode slurry is adjusted to 60±5% or the slurry viscosity is adjusted to 4000±1000cp.

[0044] The second step is coating: the slurry is evenly coated on the positive electrode current collector, and fully dried in an oven to remove the solvent in the electrode sheet, thereby obtaining a positive electrode sheet with a positive electrode film on the surface;

[0045] The third step is rolling: rolling the dried positive electrode sheet with the positive electrode film on the surface until the compaction density of the positive electrode film meets the preset compaction density value range;

[0046] Step 4: Cutting: Cut the rolled positive electrode sheet to a specified size to obtain a finished positive electrode sheet;

[0047] The fifth step is assembly: assemble the corresponding positive electrode sheets, negative electrode sheets and diaphragms according to the process of stacking, welding and shelling.

[0048] Step 6: Formation: The above-mentioned battery is dried, injected, and formed to obtain a finished battery.

[0049] The steps or raw materials not mentioned in the above method can adopt the methods or raw materials used in the prior art.

[0050] The prepared sodium battery was tested and the performance of each group of batteries was compared. The specific data are shown in the following table. By comparing the data in Table 1, it is found that compared with Comparative Example 1, after Zn doping, Example 1 has the same capacity, the rate and cycle are significantly improved, and the pH value is also reduced; after Zn and Mg co-doping, Example 2 has the same capacity, the rate and cycle are further improved, and the pH value is further reduced.

[0051] Table 1 Comparison of O3-type sodium ion positive electrode materials before and after cation doping modification

[0052] 0.2C gram capacity mAh / g 1C / 0.2C(ratio) 0.2C 50 cycles pH Comparative Example 127 93.2% 89.8% 12.92 Example 1 126.9 95.1% 93.7% 12.78 Example 2 126.8 96.4% 95.8% 12.62

[0053] In order to further study the effect of sodium content on residual alkali and circulation, the sodium content was further reduced to 0.85 (Example 3) and 0.8 (Example 4) on the basis of Example 1. Table 2 shows that the sodium content affects the residual alkali on the surface of the material. Reducing the sodium content reduces the gram capacity of the material on the one hand, and reduces the pH value on the surface of the material on the other hand, thereby further improving the rate and cycle. It can be seen that by adjusting the sodium content and increasing the doping of metal ions, the positive electrode material can be regulated in many aspects, which has a significant effect on improving the cycle, rate and reducing the moisture content of the material, thereby improving the overall performance of the sodium battery.

[0054] Table 2 Comparison of the sodium content reduction of O3 type sodium ion positive electrode materials before and after implementation

[0055]

[0056] Example 6: Effect of optimizing electrode components on sodium batteries

[0057] In order to further improve the electrode processing performance of the modified sodium ion positive electrode material active substance, the battery performance is improved by optimizing the electrode formula. The optimization method proposed in this embodiment is to adjust the composition of the binder in the positive electrode slurry, and the positive electrode active material composition includes:

[0058] The positive electrode active material is Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Mg 0.05O2, the conductive agent is a composite of superconducting carbon black (superP), carbon nanotubes (CNT) and graphene (graphene) (including 75% superconducting carbon black, 20% carbon nanotubes, and 5% graphene), and the binder and solvent are N-methylpyrrolidone (NMP). Among them, the preset mass ratio of active material, conductive agent and binder is: (94±2): (2±1.0): (4±1.0). Among them, the binder in comparative example 2 is polyvinylidene fluoride (PVDF), and the binder in the optimized positive electrode materials 1-5 is a mixture of polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN), and the mixing ratios are 80%:20%, 60%:40%, 50%:50%, 40%:60% and 20%:80% respectively.

[0059] The prepared positive electrode active material was assembled into sodium batteries according to the method of Example 5, and the battery performance was tested. The results are shown in Table 3.

[0060] Table 3 Comparison of O3 type sodium ion modified cationic cathode material electrode before and after optimization

[0061]

[0062] By comparing Table 3, it is found that compared with Comparative Example 2, the bonding strength of the pole piece is significantly improved after the mixed glue is used for the optimized positive electrode material, but the brittleness of the pole piece increases with the increase of PAN. After comparison, the cycle performance of the battery is best at a ratio of 40% PVDF + 60% PAN mixed glue.

[0063] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A doped and modified sodium ion layered metal oxide positive electrode material, characterized in that: The active substance is material Na z Ni 0.3 Fe 0.3 Mn 0.3 A x B y O2, x+y=0.1, 0≤x≤0.1, 0≤y≤0.1, 0.8≤z≤0.9; wherein A and B are one of Al, Cu, Mg, Zn, Co, Ca, B, Ti, Zr, Sn, Mo, W, Tc, Nb, Ag, V, Ba and Sr.

2. The doped and modified sodium ion layered metal oxide positive electrode material according to claim 1, characterized in that: After the raw materials of the active material are mixed, they are placed in an air atmosphere or an oxygen atmosphere and baked at 900° C. The flow rate of the air atmosphere or the oxygen atmosphere is adjusted to adjust the active material of the positive electrode material.

3. The doped and modified sodium ion layered metal oxide positive electrode material according to claim 2, characterized in that: The flow rate adjustment parameter is set to 3-5m / s for the upper atmosphere valve flow rate. 3 / h, the flow rate of the lower atmosphere valve is set to 4-7m 3 / h.

4. A sodium ion battery positive electrode comprising the positive electrode material according to any one of claims 1 to 3.

5. The sodium ion battery positive electrode according to claim 4, characterized in that: The slurry for preparing the positive electrode also includes superconducting carbon black, carbon nanotube and graphene composite conductive agent, adhesive and solvent; wherein the mass ratio of active material, conductive agent and adhesive is 92-96:1-3:3-5.

6. The sodium ion battery positive electrode according to claim 5, characterized in that: The adhesive is a mixture of polyvinylidene fluoride and polyacrylonitrile, and the mixing ratio is 1:0.25-4.

7. The sodium ion battery positive electrode according to claim 6, characterized in that: The mixing ratio of polyvinylidene fluoride and polyacrylonitrile in the adhesive is 4:

6.

8. The sodium ion battery positive electrode according to claim 5, characterized in that: The solvent is N-methylpyrrolidone.

9. A sodium ion battery, characterized in that: The invention comprises a sodium ion battery positive electrode as described in any one of claims 4 to 8.

Citation Information

Patent Citations

  • Double-layer coated layered oxide material as well as preparation and application thereof

    CN115911394A

  • Sodium-ion battery positive electrode material, preparation method and application thereof, and sodium-ion battery

    CN116154138A

  • Sodium ion secondary battery positive electrode slurry and preparation method thereof

    CN116207262A

  • Composite electrode plate, preparation method and sodium ion battery

    CN116598425A

  • Doped and modified P2 type sodium ion layered metal oxide positive electrode material and preparation method thereof

    CN116598493A